The neuronal splicing factor Nova co-localizes with target RNAs in the dendrite - Racca, Claudia; Gardiol, Alejandra; Eom, Taesun; Ule, Jernej; Triller, Antoine; Darnell, Robert B. (Frontiers in Neural Circuits, 2010)
Nova proteins are neuron-specific RNA binding proteins targeted by autoantibodies in a disorder manifest by failure of motor inhibition, and they regulate splicing and alternative 3′ processing. Nova regulates splicing of RNAs encoding synaptic proteins, including the inhibitory glycine receptor α2 subunit (GlyRα2), and binds to others, including the GIRK2 channel. We found that Nova harbors functional NES and NLS elements, shuttles between the nucleus and cytoplasm, and that 50% of the protein localizes to the soma-dendritic compartment. Immunofluoresence and EM analysis of spinal cord motor neurons demonstrated that Nova co-localizes beneath synaptic contacts in dendrites with the same RNA, GlyRα2, whose splicing it regulates in the nucleus. HITS-CLIP identified intronic and 3′ UTR sites where Nova binds to GlyRα2 and GIRK2 transcripts in the brain. This led directly to the identification of a 3′ UTR localization element that mediates Nova-dependent localization of GIRK2 in primary neurons. These data demonstrate that HITS-CLIP can identify functional RNA localization elements, and they suggest new links between the regulation of nuclear RNA processing and mRNA localization.